2007
DOI: 10.1175/jas3951.1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies and Universality of Buoyancy-Dominated Turbulent Fluctuations: A Large-Eddy Simulation Study

Abstract: Turbulent fluctuations of both velocity and temperature fields, issuing from high-resolution large-eddy simulations, have been analyzed in convective boundary layers. The numerically simulated flows are strongly anisotropic at large scales: this is due both to the action of buoyancy and to the imposed geostrophic wind. Their relative weight is varied so that one experiment's results are much more convective than the other. To properly disentangle anisotropic properties, the authors exploit both standard statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…A similar conclusion was drawn by Antonelli et al (2007) for buoyancy-dominated turbulent flows in the atmospheric convective boundary layer.…”
Section: Spatial and Temporal Scaling Laws Of Structure Functions Andsupporting
confidence: 85%
“…A similar conclusion was drawn by Antonelli et al (2007) for buoyancy-dominated turbulent flows in the atmospheric convective boundary layer.…”
Section: Spatial and Temporal Scaling Laws Of Structure Functions Andsupporting
confidence: 85%
“…Despite the possible anisotropy of the flow, studies of the convective ABL seem to indicate a sort of recovery of isotropic behavior at smaller scales [24,25]. Large eddy simulations have shown that this tendency seems to be a "genuine feature" in the inertial sub-range for both passive scalar fields and flow velocity, and due neither to sub-grid scale nor to finite size effects [26]. These results seems to indicate that the statistical behavior of the ABL can be described by the same set of (isotropic) scaling exponents and multifractal parameterization even for flows characterized by different degreess of convection [24,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…However, some studies indicate that even in strongly anisotropic flows, a sort of recovery of isotropy may exist at smaller scales [18][19][20]. Large eddy simulations have shown that isotropy recovery is a "genuine feature" of the inertial sub-range [21,22]. The statistical properties of homogeneous and isotropic turbulence are usually characterized by means of energy spectral density and by the anomalous scaling of the structure functions of the field increments, e.g., S q ∝ ζ(q) [23][24][25][26], correlations [27][28][29][30]; or in terms of multifractality from the analysis of the so called multifractal spectrum f (α) [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%